2018
DOI: 10.15171/jhp.2018.34
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydroalcoholic extract of Urtica dioica on morphine withdrawal signs in male mice

Abstract: The present study findings showed that Urtica dioica extract could decrease the morphine withdrawal signs and might be beneficial in addicted patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Nonetheless, other studies have assessed and confirmed the safety of these extracts. Asadi and Abbasi Maleki demonstrated the LD 50 of hydroalcoholic extract U. dioica in mice as 2900 mg/kg during acute toxicity testing, much higher than the doses used in our experiment (52). Similarly, P. boissieriana extract given to mice models at doses of 500 and 1000 mg/kg showed no reported side effects or mortalities (21,53).…”
Section: Discussionmentioning
confidence: 42%
“…Nonetheless, other studies have assessed and confirmed the safety of these extracts. Asadi and Abbasi Maleki demonstrated the LD 50 of hydroalcoholic extract U. dioica in mice as 2900 mg/kg during acute toxicity testing, much higher than the doses used in our experiment (52). Similarly, P. boissieriana extract given to mice models at doses of 500 and 1000 mg/kg showed no reported side effects or mortalities (21,53).…”
Section: Discussionmentioning
confidence: 42%
“…With this in mind, previous studies have demonstrated that the GABAergic system performs a pivotal function in opioid addiction. Moreover, studies have shown that positive modulators on the benzodiazepine site in the GABAA receptors (e.g., diazepam) and selective GABAA receptor agonists (e.g., muscimol) pacify morphine withdrawal signs (6,19,20,27).…”
Section: Discussionmentioning
confidence: 99%
“…In order to induce morphine tolerance or dependence, this compound was administered i.p. three times daily at 8 a.m. (50 mg/kg), 12 p.m. (50 mg/kg), and 4 p.m. for 3 continuous days, followed by the administration of a single dose (50 mg/kg) on day 4 before administration of naloxone (19,20).…”
Section: Induction Of Tolerance and Dependencementioning
confidence: 99%
See 1 more Smart Citation